PENDAMPINGAN SEBAGAI WUJUD AKSI PASTORAL TERHADAP PASIEN HIV/AIDS DI YAYASAN BATEMANG PLUS MANADO - Frieska Putrima Tadung; Heliyanti Kalintabu; Randy A.A.P Lombogia; Harlinda Losoh Putri Agama (POIMEN Jurnal Pastoral Konseling, 2024)
Human Immunodeficiency Virus (HIV) is a virus that attacks the human immune system and weakens the body's ability to fight any disease that arises. Common symptoms include persistent fever, cough and diarrhoea. This collection of disease symptoms due to the weakening of the immune system is called AIDS (Acquired Immune Deficiency Syndrome). The HIV virus is present in body fluids, especially blood, semen, vaginal fluids, and breast milk. The virus damages the human immune system, causing a decrease or loss of immunity, making the body more susceptible to HIV/AIDS infection. This can lead to a variety of problems, including physical, social, emotional, mental and spiritual problems. Pastoral care is the realisation and representation of the universal human family caring nature. Pastoral care is a service of help and healing from the church, both individually and in groups so that they can grow in the process of living in society. It can be said that pastoral care is done intentionally for those who are experiencing problems or struggles in life. Pastoral care is an answer to everyone's need for warmth, care, support, and shepherding and accompaniment